Penerapan Model Pembelajaran Role Playing Berbantuan Media Komik terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri 1 Widodo - Sartika, Inayah Hani; Mulyono, Dodik; Raflesia, Citra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the completion of IPA learning outcomes for five grade students at SD Negeri 1 Widodo. The research method used is in the form of Pre-Experimental Design. The population was all third grade students at SD Negeri 1 Widodo and at the same time the research sample totaling 24 students. Data collection was carried out using saturated sampling technique. The data collected was analyzed using a test. Based on the results of data analysis with a significant level of α = 5% and dk = 23, it shows that Zcount = 3.53 and Ztable = 1.64 (Zcount > Ztable). Thus it can be concluded that the IPA learning outcomes of class V students at SD Negeri Widodo after the Role Playing learning model assisted by comic media are significantly complete. The average student final test score was 78,46 and the percentage of students who passed was 20 students (83,33%). Keywords: IPA, Komic, Learning Model, Role Playing.